End-to-end learning, and audio-visual human-centric video understanding - Brown, A (2022)
The field of machine learning has seen tremendous progress in the last decade, largely due to the advent of deep neural networks. When trained on large-scale labelled datasets, these machine learning algorithms can learn powerful semantic representations directly from the input data, end-to-end. End-to-end learning requires the availability of three core components: useful input data, target outputs, and an objective function for measuring how well the model's predictions match the target outputs. In this thesis, we explore and overcome a series of challenges as related to assembling these three components in the sufficient format and scale for end-to-end learning.